2022
DOI: 10.1002/1878-0261.13259
|View full text |Cite
|
Sign up to set email alerts
|

PGAM1 regulation of ASS1 contributes to the progression of breast cancer through the cAMP/AMPK/CEBPB pathway

Abstract: Phosphoglycerate mutase 1 (PGAM1) is a crucial glycolytic enzyme, and its expression status has been confirmed to be associated with tumor progression and metastasis. However, the precise role and other biological functions of PGAM1 remain unclear. Here, we report that PGAM1 expression is upregulated and related to poor prognosis in patients with breast cancer (BC). Functional experiments showed that knockdown of PGAM1 could suppress the proliferation, invasion, migration, and epithelial–mesenchymal transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The PI3K-Akt signaling pathway regulates tumor cell proliferation and inhibits apoptosis [ 47 49 ] in various types of tumors, and is associated with lung cancer lymph node micrometastasis [ 50 ]. Similarly, cAMP, as a second messenger in the body, directly regulates cell metabolism, growth, and apoptosis, thereby promoting tumor progression [ 51 , 52 ]. Additionally, while cell adhesion molecules are often linked to tumor metastasis, it is possible that cancer cells have already begun to disseminate or even micro-metastasize in the early stages, as observed in early breast cancer patients with metastatic tumor cells in the bone marrow [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K-Akt signaling pathway regulates tumor cell proliferation and inhibits apoptosis [ 47 49 ] in various types of tumors, and is associated with lung cancer lymph node micrometastasis [ 50 ]. Similarly, cAMP, as a second messenger in the body, directly regulates cell metabolism, growth, and apoptosis, thereby promoting tumor progression [ 51 , 52 ]. Additionally, while cell adhesion molecules are often linked to tumor metastasis, it is possible that cancer cells have already begun to disseminate or even micro-metastasize in the early stages, as observed in early breast cancer patients with metastatic tumor cells in the bone marrow [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphoglycerate mutase 1 (PGAM1) is a crucial glycolytic enzyme, and its expression status has been confirmed to be associated with tumor progression and metastasis [22]. Previous study has demonstrated target PGAM1 could inhibit the cell migration [8].…”
Section: Discussionmentioning
confidence: 99%
“…In cancer biology, PGAM1 has garnered attention due to its association with tumorigenesis, tumor progression, and therapeutic resistance [ 44 ]. Several studies have demonstrated that PGAM1 is frequently upregulated in various types of cancers, including lung, breast, colorectal, and liver cancers [ 45 , 46 ]. Elevated expression of PGAM1 is often correlated with aggressive tumor phenotypes, poor prognosis, and reduced patient survival rates [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that PGAM1 is frequently upregulated in various types of cancers, including lung, breast, colorectal, and liver cancers [ 45 , 46 ]. Elevated expression of PGAM1 is often correlated with aggressive tumor phenotypes, poor prognosis, and reduced patient survival rates [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation